The Australian purchase of three United States guided missile destroyers: A study of the defense aspect of Australian-American relations - Wallace, Roy Neil (Tufts Archival Research Center, 2014)
Abstract: The objectives of this dissertation are to a. contribute to the body of scholarly knowledge on Australia and, in particular, its political and national security situation; b. identify the causes and effects of the transfer of a modern combatant ship to a nation which had not previously had United States ships in its fleet; c. improve the understanding of security aspects of alliance relationships.